The factors affecting the extraction condition for neuroprotective activity of centella asiatica evaluated by metal chelating activity assay - Amid, Azura; Mohd Salim, Roshan Jahn; Adenan, Mohd Ilham (Asian Network for Scientific Information, 2010)
The study was aimed to evaluate the metal chelating activity of CA which will first be assessed for neuroprotective property. Further, response surface methodology will be used to optimize the extraction parameters to yield an optimum metal chelating activity of CA by minimizing the cost of extraction. Centella asiatica (CA) is a rich antioxidant candidate was studied for its potential as a neuroprotective agent to fight against oxidative damage caused by Reactive Oxygen Species (ROS) towards neuronal cells which eventually lead to neurodegenerative diseases such as Alzheimer’s and Parkinson disease. The limited number of neuroprotective study carried out so far indicated that metal (iron) chelation therapy could be a viable neuroprotective approach for neurodegenerative disorders. Methanolic and aqueous extract of CA was obtained by conventional soxhlet extraction (temperature: 40-60°C, ratio: 1:30 (w/v), time: 24 h). The IC50 of methanolic and aqueous extract obtained was 0.26 and 0.69 mg mL-1, respectively. Further, Response surface methodology was used to determine the optimum CA extraction condition that gives optimum metal chelating activity. Experiments were designed according to central composite design with four factors (time, temperature, ratio of raw material to solvent and agitation speed) and six central points that derived total 30 runs. In conclusion, run 17 (temperature: 25°C, ratio: 1:45 (w/v), time: 1.5 h and speed: 200 rpm) gave the optimum chelating activity with IC50 0.093 mg mL-1.